2017
DOI: 10.2139/ssrn.3088763
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding Public Goods: An Experiment

Abstract: We assess the impact of different crowdfunding designs on the success of crowdfunded public goods using a lab-in-the-field experiment. Our design treatments aim to increase the efficiency of crowdfunding campaigns by raising aggregate contributions and decreasing possible coordination problems that may occur when potential donors are faced with a multitude of projects seeking contributions. Amongst others, we explore the potential of seed money and the impact of the attraction effect. Using a four-day time win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The follow-up experimental studies of Bagnoli and McKee (1991) and Bagnoli et al (1992) demonstrate lower efficiency rates for multiple public good projects. Recently, Corazzini et al (2015) and Ansink et al (2017) have confirmed the same outcome of lower provision rates for multiple public goods.…”
Section: Onmentioning
confidence: 72%
“…The follow-up experimental studies of Bagnoli and McKee (1991) and Bagnoli et al (1992) demonstrate lower efficiency rates for multiple public good projects. Recently, Corazzini et al (2015) and Ansink et al (2017) have confirmed the same outcome of lower provision rates for multiple public goods.…”
Section: Onmentioning
confidence: 72%
“…The data analysis accounts for the period number and treatment ordering to verify that the main conclusions are not sensitive to these small procedural variations. We did not include alternative projects with identical refund bonus conditions, or both with no refund bonus, because previous research (Corazzini et al, 2015(Corazzini et al, , 2020Ansink et al, 2017;Cason and Zubrickas, 2019) has already investigated coordination and contributions to multiple projects with similar or identical characteristics.…”
Section: Experimental Designmentioning
confidence: 99%
“…Several recent papers consider related extensions of this framework. Ansink et al (2017) considers the impact of seed money on contributions and extends the framework to allow for giving in continuous time. Cason and Zubrickas (2018) and Liu et al (2016) considers the impact of rebates when a public good fails to achieve its threshold on contributions in a multiple good setting.…”
Section: Literature Reviewmentioning
confidence: 99%